2020
DOI: 10.3390/su12177103
|View full text |Cite
|
Sign up to set email alerts
|

Performance-Based Building Design of High-Rise Residential Buildings in Indonesia

Abstract: The complexity of the design and completion of buildings poses a challenge for the construction industry in terms of meeting user needs. Performance-based building design (PBBD) is a design concept that describes these needs as performance requirements, designing buildings according to an iterative process of translating and evaluating the performance requirements of the buildings. PBBD is a concept that is used to produce buildings with high performance. This study aims to identify which PBBD factors are appl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 53 publications
(86 reference statements)
0
20
0
Order By: Relevance
“…Table 5 presents the distribution of data using mean and standard deviation for six variables in this study. From the acquisition of mean and standard deviation, the analysis obtained a mean value of more than 3 for the mean value of six variables ranging from 3.1364 to 4.3068, which means respondents agree that all variables are important [44]. However, the interests of each of these variables were perceived differently by each respondent of each project stakeholder.…”
Section: Results Of Distributing Datamentioning
confidence: 98%
See 1 more Smart Citation
“…Table 5 presents the distribution of data using mean and standard deviation for six variables in this study. From the acquisition of mean and standard deviation, the analysis obtained a mean value of more than 3 for the mean value of six variables ranging from 3.1364 to 4.3068, which means respondents agree that all variables are important [44]. However, the interests of each of these variables were perceived differently by each respondent of each project stakeholder.…”
Section: Results Of Distributing Datamentioning
confidence: 98%
“…The most important variables in this study were identified by considering rankings based on respondents' preferred scores. Variables are considered important if they have a mean score of more than 3, which means that respondents agree that all variables are important [44]. Mean and SD are also used to provide patterns of respondent perception at the beginning before factor analysis is performed, because in practice, every stakeholder has different characteristics, interests, and business fields.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Data were collected using a questionnaire and then analyzed using regression analysis. This research is a development from previous research [8]. Thus, this paper can contribute not only to increasing theoretical knowledge, but also in providing an optimal design strategy for retail property.…”
Section: Introductionmentioning
confidence: 83%
“…In the process of planning and designing building performance, Performance-based Building Design (PBBD) is a concept that can be used to provide an overview of how buildings can operate so that the utilization of retail property space is optimal, comfortable and safe for user/occupant. There are four factors in implementing PBBD according to research [8]. They are the occupant interests, building management, the process of design collaboration and risk of loss.…”
Section: Introductionmentioning
confidence: 99%
“…Public construction projects have a huge impact on the national economy, and the occurrence of disasters during construction results in incalculable social costs and life and property losses [16,17]. Moreover, the quality of risk management has a dramatic impact on the operational quality of the facility upon completion of the project [18].…”
Section: Introductionmentioning
confidence: 99%